Pharmacological treatments for generalised anxiety disorder: a systematic review and network meta-analysis. Issue 10173 (23rd February 2019) - Slee, April; Nazareth, Irwin; Bondaronek, Paulina; Liu, Yifeng; Cheng, Zhihang; Freemantle, Nick
Summary: Background: Generalised anxiety disorder is a disease that can be associated with substantial dysfunction. Pharmacological treatment is often the first choice for clinicians because of the cost and resource constraints of psychological alternatives, but there is a paucity of comparative information for the multiple available drug choices. Methods: A systematic review and network meta-analysis was performed on randomised trials in adult outpatients with generalised anxiety disorder identified from MEDLINE, Web of Science, Cochrane Library, ClinicalTrials.gov, Chinese National Knowledge Infrastructure (CNKI), Wanfang data, Drugs@FDA and commercial pharmaceutical registries. Placebo and active control trials were included. Data were extracted from all manuscripts and reports. Primary outcomes were efficacy (mean difference [MD] in change in Hamilton Anxiety Scale Score) and acceptability (study discontinuations for any cause). We estimated summary mean treatment differences and odds ratios using network meta-analyses with random effects. This study is registered with PROSPERO, number CRD42018087106. Findings: Studies were published between Jan 1, 1994 and Aug 1, 2017, in which 1992 potential studies were screened for inclusion. This analysis is based on 89 trials, which included 25 441 patients randomly assigned to 22 different active drugs or placebo. Duloxetine (MD −3·13, 95% credible interval [CrI] −4·13 to −2·13), pregabalin (MD −2·79, 95% CrI −3·69 to −1·91), venlafaxine (MD −2·69, 95% CrI −3·50 to −1·89), and escitalopram (MD −2·45, 95% CrI −3·27 to −1·63) were more efficacious than placebo with relatively good acceptability. Mirtazapine, sertraline, fluoxetine, buspirone, and agomelatine were also found to be efficacious and well tolerated but these findings were limited by small sample sizes. Quetiapine (MD −3·60 95% CrI −4·83 to −2·39) had the largest effect on HAM-A but it was poorly tolerated (odds ratio 1·44, 95% CrI 1·16–1·80) when compared with placebo. Likewise, paroxetine and benzodiazepines were effective but also poorly tolerated when compared with placebo. Risk of reporting bias was considered low, and when possible all completed studies were included to avoid publication bias. Interpretation: To our knowledge, this is the largest contemporary review of pharmacological agents for the treatment of generalised anxiety disorder by use of network analysis. There are several effective treatment choices for generalised anxiety disorder across classes of medication. The failure of initial pharmacological therapy might not be a reason to abandon a pharmacological treatment strategy. Funding: No funding was received for this research.